On Generalized Regular Continuous Functions In Topological Spaces - Mahmood, S. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we introduce a new type of functions called the generalized regular continuous functions .These functions are weaker than regular continuous functions and stronger than regular generalized continuous functions. Also, we study some characterizations and basic properties of generalized regular continuous functions .Moreover we study another types of generalized regular continuous functions and study the relation among them